Customer Based Brand Equity and University Brand Management - Viet Dung, Tran (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 35 No 4, 2019)
As Vietnam integrated deeply into the world economy, higher institutions are on a rise and faced with strong competition, university brand management has played an increasingly important role. Following brand equity theories and customer based brand equity models, the paper proposes an analytical framework which adopts Aeker’s four components (1991) including brand awareness, brand associations, perceived quality and brand loyalty in order to enhance the value of brand equity for higher institutions in Vietnam.